Carcass Characteristics of Lavender, Pearl Grey and Royal Purple Varieties of Domesticated Helmeted Guinea Fowl (Numida meleagris) Raised under Intensive Management System in Botswana - Kgakole, Boitumelo; Nsoso, Shalaulani James; Kgwatalala , Patrick Monametsi (International Journal of Poultry Science, 2016)
The objective of this study was to evaluate carcass characteristics of lavender, pearl gray and royal purple varieties of domesticated helmeted guinea fowl kept under an intensive management system in Botswana. Carcass traits of 35 lavender, 27 royal purple and 39 pearl grey helmeted guinea fowl varieties were evaluated at 20 weeks of age. Carcass traits measured included live weight, carcass weight, primal cuts (breast, back, thigh, drumstick, wing, neck, shank and head) weights, giblets (gizzard, liver and heart) weight and feather weight. There were no significant differences (p>0.05) in live weight, carcass weight and dressing percentage between males and females of different varieties of domesticated helmeted guinea fowl at slaughter age of 20 weeks. There were also no significant sex differences in giblets weight and primal cuts weights in all the three varieties except for drumstick weight which was significantly higher in pearl grey males (65.57±1.35 g) than females (58.08±1.46 g). Males of pearl grey and royal purple varieties had higher live weight, carcass weight, primal cuts weight and giblets weight than their female counter parts while the opposite was true for the lavender variety. There were no significant differences in live weight, carcass weight, dressing percentage, giblets weight and primal cuts weights except for drumstick weight and shank weight between males of the three varieties of helmeted guinea fowl. Royal purple males had significantly higher drumstick weight (73.57±1.91 vs 63.18±1.35 g) and shank weight (19.71±0.57 vs 17.29±0.40 g) than their lavender counterparts. There were also no significant differences in live weight, carcass weight, dressing percentage, giblets weight and primal cuts weights between females of the three varieties of helmeted guinea fowl. Royal purple and lavender females had significantly higher drumstick weight (67.27±1.52 and 65.91±1.52 g, respectively) than their pearl grey counterparts (58.08±1.46 g).